2022
DOI: 10.1097/rnj.0000000000000388
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cooling Therapies on Fatigue, Physical Activity, and Quality of Life in Multiple Sclerosis

Abstract: Purpose: This meta-analysis examined the effects of the cooling therapies on fatigue, physical activity, and quality of life (QoL) in patients with multiple sclerosis (MS). Methods: Articles published between 2000 and 2020 were searched in six databases. The standardized mean differences were determined by the upper and lower limits of 95% confidence intervals. Publication bias was assessed by conducting the Egger test, which uses linear regression. Publication bias was examined visually using a funnel plot. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Active and passive cooling methods have been used as a complimentary therapeutic approach to address symptoms sensitive to temperature (353), with no specific cooling garment identified as superior (354). The benefits of cooling therapies have been reported in physical activity and function, fatigue, and the QoL in individuals with MS (354,355).…”
Section: Other Interventionsmentioning
confidence: 99%
“…Active and passive cooling methods have been used as a complimentary therapeutic approach to address symptoms sensitive to temperature (353), with no specific cooling garment identified as superior (354). The benefits of cooling therapies have been reported in physical activity and function, fatigue, and the QoL in individuals with MS (354,355).…”
Section: Other Interventionsmentioning
confidence: 99%
“…It has been shown that up to 60-80% of people with MS experience a worsening of their symptoms when they are subjected to higher ambient temperatures and/or increased core body temperatures, such as during exercise (Uhthoff's phenomenon) [105,106]. On the other hand, several studies showed that cooling can enhance the motor abilities of MS patients and may improve some MS symptoms [41,60,[107][108][109].…”
Section: Physical Functional and Psychological Parametersmentioning
confidence: 99%
“…Even Uthoff's syndrome, characterized by a temporary worsening of MS-related neurological symptoms due to increased core body temperature, may be managed effectively through exercise combined with cooling strategies [10,11]. These strategies, when applied before or during exercise, can prevent a rise in both core and skin temperatures, thereby enhancing the safety and effectiveness of exercise programs for individuals with MS. Research has demonstrated that such cooling strategies can significantly mitigate the risk of symptom exacerbation, enabling a more comfortable and beneficial physical activity experience for those affected by MS [12]. This form of therapy can be an essential component of symptom management, especially for those who experience a significant worsening of symptoms with heat.…”
Section: Introductionmentioning
confidence: 99%